Development of an Omni-Directional Mobile Base Utilizing Spherical Robots as Wheels - 김동영; Kim, Doik; Kim, Jung-Hee (2017 14TH INTERNATIONAL CONFERENCE ON UBIQUITOUS ROBOTS AND AMBIENT INTELLIGENCE (URAI), 2017)
This paper proposes an omni-directional mobile base utilizing spherical robots as its wheels. In particular, the mobile base can move in an omni-directional manner by controlling translational and rotational motion of the spherical robots. However, in practice, unnecessary rotation of the spherical robots may occur due to the presence of friction and individually controlled wheel's-direction. To overcome such difficulty, we install an inertial measurement unit (IMU) on the proposed mobile base, and therefore it is possible to correct the pose of the mobile base. Especially if we can estimate the pose of the mobile base from the IMU data, we can control the robot in a desired direction. Finally, we develop a prototype of mobile base and present the possibility of omni-directional control.